ASSESSMENT OF THE PHYSICOCHEMICAL STATUS OF A TEXTILE INDUSTRY'S EFFLUENT AND ITS ENVIRONMENT (Biological Sciences - PJSIR, 2002)
Physicochemical status of an industrial textile's effiuent and its environment (soil and agricultural product-cas sava tubers) at Ado-Ekiti , Nigeria was assessed. Results showed that great variation existed among the parameters (pH units, tempera ture, conductivity, total hardness, total alkalinity, bicarbonate and hydroxide hardness, calcium and magnesium hardness, chloride and metal elements) down the channel , significant difference (P